VIDEOGAMES AND THEIR HISTORICAL PERCEPTION ON THE WARS OF THE 20TH CENTURY - DE LA CRUZ VILLANUEVA, Carlos (2021)
The following research is the beginning of a larger work, developed under the narrative of the essay, aims to identify the most relevant aspects of video games aimed at recreating warlike events of great historical importance, such as world wars. Among the most notable aspects that this research offers is the  identification and delimitation of possible boundaries for the analysis of video games. Considering them as historical sources, since they are social creations, they recreate and generate a perception of situations or facts of reality, under the veil of fun, recreation, entertainment and fantasy. In these pages, we will approach the scope and limitations of the study of video games, through the brief observation of three of them, which set or recreate some moments of the wars of wars in the twentieth century. Through this we will observeits usefulness as a source, complement and understanding that the video industry jueguil, creates, recreates and reflects on wars in the twentieth century. This is thanks to the initial exploration from the perspective of the historian.